Water balance calculation capability of hydrological models: Review - Tran, Hop Quang; Fehér, Zoltán Zsolt (Acta Agraria Kaposváriensis, 2022)
Currently, in the world, there are many different hydrological models built and developed to solve problems related to the hydrological cycle. Each model has its specific mathematical foundations to describe physical processes in nature. Therefore, each model has its various characteristics: setting up the model, input data requirements, model calibration and verification, and output results. Water balance is still playing an important role in the effective management and use of water resources for agriculture. Based on the results of the hydrological parameter’s calculation, the water balance of the study basin can be calculated by the user or by the separated module of each model. Each hydrological models have its advantages and disadvantages. However, it is impossible to simulate hydrological processes and water balance completely accurately in nature. Still, simulation results can give us a view of the changing trend of hydrological components and the water balance. Model developers are gradually completing the shortcomings and improving the efficiency and accuracy so that the model can simulate reality with the highest accuracy. This paper sets out to review the fifteen hydrological models currently widely used in the world. Within the frame of the present study, some models are only briefly introduced; the rest are considered in more detail, from more aspects, from specific examples so that readers can decide for themselves which model is suitable for their study area and simulation needs, especially in the identity of the complex and unpredictable impacts of climate change on the agricultural sector.
Keywords: Integrated watershed modelling; water balance